2020
DOI: 10.1007/s11423-020-09891-1
|View full text |Cite
|
Sign up to set email alerts
|

Considering the emotional needs of students in a computer-based learning environment

Abstract: This paper is in response to the manuscript entitled, "Success, failure and emotions: Examining the relationship between performance feedback and emotions in diagnostic reasoning," (Jarrell et al. in Educ Technol Res Dev 65:1263-1284, 2017) from a K-12 student perspective. Jarrell et al.'s (2017) noted a strong relationship between outcome emotions and performance tasks where high performing medical students resulted in the most positive emotions. Researchers indicated that medical students who experienced neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The results showed that students in the smart technology schools obtained more passes, and the mean scores from the designed questions were also higher than in the non-smart technology schools (Moussa et al, 2020). This success could be attributed to the flexibility and interactive nature of smartboard integration (Davidovitch & Yavich 2017), particularly immediate feedback while using the smartboard (Moore, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that students in the smart technology schools obtained more passes, and the mean scores from the designed questions were also higher than in the non-smart technology schools (Moussa et al, 2020). This success could be attributed to the flexibility and interactive nature of smartboard integration (Davidovitch & Yavich 2017), particularly immediate feedback while using the smartboard (Moore, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Davidovitch and Yavich (2017) further reiterated that by teaching with a smartboard, learning becomes flexible and interactive through different learning opportunities. Immediate feedback, for example, is one of the opportunities smartboards provide to promote learning, which might be challenging in a traditional classroom (Moore, 2021). Through interaction with the technology, teacher performance and student learning are improved (Tyagi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Computer-based educational technology has been widely recognized as an effective and critical intervention to improve student learning in a variety of academic disciplines in science, technology, engineering, and mathematics (STEM) (Moore, 2021; Sanders & George, 2017; Schindler et al, 2017; Wang et al, 2018). An important computer-based educational technology is computer simulation and animation (CSA), where real-world physical phenomena and processes are simulated and animated with computer programs and shown on computer screens.…”
Section: Introductionmentioning
confidence: 99%